2001
DOI: 10.1111/j.1749-6632.2001.tb03797.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Anomalies in Women with Endometriosis

Abstract: Endometriotic lesions are defined by extrauterine growth of endometrial glands and stroma. Retrograde menstruation with subsequent attachment, invasion, and neovascularization are believed to give rise to the endometriotic lesions. As most women exhibit some degree of retrograde menstruation, some other unidentified factor(s) must render certain women susceptible to attachment and growth of ectopic endometrial tissue. A variety of theories have been proposed to account for this susceptibility, including geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(94 citation statements)
references
References 77 publications
6
75
1
12
Order By: Relevance
“…For some time, endometriosis research has focused on comparisons of various physiological processes in the endometrium (ectopic vs eutopic) of women affected by endometriosis, against unaffected women (Sharpe-Timms 2001). This has identified multiple anomalies in genetic, environment, angiogenic, endocrine, metabolic and immunological mechanisms.…”
Section: Endometriosis and The Neoplastic Processmentioning
confidence: 99%
“…For some time, endometriosis research has focused on comparisons of various physiological processes in the endometrium (ectopic vs eutopic) of women affected by endometriosis, against unaffected women (Sharpe-Timms 2001). This has identified multiple anomalies in genetic, environment, angiogenic, endocrine, metabolic and immunological mechanisms.…”
Section: Endometriosis and The Neoplastic Processmentioning
confidence: 99%
“…The cysts in rats and women share many structural and molecular features (58). The growths contain or evoke abnormal production in nearby tissues of many substances that have been hypothesized to play as yet unspecified roles in the signs and symptoms of ENDO.…”
mentioning
confidence: 99%
“…These include the expression of several ATRAregulated genes and cytokines that are aberrantly expressed in eutopic endometrium of women with endometriosis, including matrix metalloproteinases, tumor necrosis factor-b, interleukin (IL)-6, IL-11, various integrins, bax, and fas ligand. [48][49][50] As such, a number of seemingly discordant features of endometriosis including decreased cell death, increased growth and migration, and enhanced invasive properties of intraperitoneally seeded endometrial cells could be accounted for by dysregulation of ATRA synthesis in endometrial tissue. In further support of this concept, it has recently been shown that endometriotic tissue is characterized by a gene expression pattern that is consistent with a decrease in ATRA synthesis and/or action in situ.…”
Section: Discussionmentioning
confidence: 99%